Effects of preslaughter stress levels on the post-mortem sarcoplasmic proteomic profile of gilthead seabream muscle - Silva, Tomé S. (2014)
Fish welfare is an important concern in aquaculture, not only due to the ethical implications but also for productivity and quality-related reasons. The purpose of this study was to track soluble proteome expression in post-mortem gilthead seabream muscle and to obsere how preslaughter stress affects these post-mortem processes. For the experiment, two groups of gilthead seabream (n = 5) were subjected to distinct levels of preslaughter stress, with three muscle samples being taken from each fish. Proteins were extracted from the muscle samples, fractionated, and separated by 2DE. Protein identification was performed by MALDI-TOF-TOF MS. Analysis of the results indicates changes on several cellular pathways, with some of these changes being attributable to oxidative and proteolytic activity on sarcoplasmic proteins, together with leaking of myofibrillar proteins. These processes appear to have been hastened by preslaughter stress, confirming that it induces clear postmortem changes in the muscle proteome of gilthead seabream.